EXPERIENCE STUDY: EFFECT OF UNDERWRITING METHODS ON MORTALITY RATE FOR LIFE INSURANCE PRODUCT AT PT. ABC (2015-2020 PERIOD) - Imani, Alvira Adya; Hikmah, Yulial (PATTIMURA UNIVERSITY, 2022)
In creating complex mortality tables, some insurance companies do not have enough data to build credible tables based on their experiences. Therefore, insurance companies usually carry out their analysis by comparing the company's actual mortality rate with the expected mortality rate based on industry tables, which is the